PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN KOMPETENSI TERHADAP KINERJA PERSONEL ESELON PEMBANTU PIMPINAN DI RESIMEN X - Wisnu Wibowo; M Al-Amin; Zulhawati Zulhawati; Bambang Moertono Setiawan; Nur Wening (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
Staff performance is very important for an organization because it shows how organization perform to achieve their goals. As an organizational resource that has feelings and thoughts, there are a lot of things that can affect staff performance such as organizational culture, motivation, and competency. Therefore, the aim of this study is to examine the influence of organizational culture, motivation, and competency to performance of staff at Resimen X. The method used in this research is quantitative method by using mulitiple linear regression equation. Data was obtained from 42 respondents at administration and logistics department, security and operation department, education assessment department, and education department of Resimen X by using questionnaire. The sampling technique used in this research is saturated samples. The results of this research shows that organizational culture, motivation, and competency simultaneously have significant influence to performance (28,978 > 4,34) with coefficient of determination is 69,6%. As partial results, organizational culture has no significant influence to performance (- 0,914 < 2,024), motivation has significant influence to performance (5,425 > 2,024), and competency has no significant influence to performance (1,551 < 2,024). Keywords: organizational culture, motivation, competency, and performance.